2020
DOI: 10.21037/tau.2020.03.08
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of red cell distribution width in bladder cancer

Abstract: Background: Bladder cancer is one of the most common cancers worldwide. It ranks ninth among all cancers and fourth among cancers in male patients. Recent studies reported that red blood cell (RBC) distribution width (RDW) was a potential predictor in some cancers. This study explored the significance of RDW in patients with bladder cancer after radical cystectomy. Methods: This study involved 169 patients who underwent radical cystectomy between March 2009 and October 2018. The overall survival (OS), cancer-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…RDW level may change as a result of blood diseases, infectious diseases, malnutrition, and even germline mutations associated with CRC (20)(21)(22). Additionally, studies have revealed that elevated RDW level was an independent risk factor for unfavorable survival in patients with CRC and bladder cancer (13)(14)(15). Consistent with the previous studies, the results of this study revealed that preoperative elevated RDW-SD level was an unfavorable predictor of PFS and elevated RDW-CV level was related to postoperative complications in patients with CRLM.…”
Section: Nomogram For Os Predictionsupporting
confidence: 90%
See 1 more Smart Citation
“…RDW level may change as a result of blood diseases, infectious diseases, malnutrition, and even germline mutations associated with CRC (20)(21)(22). Additionally, studies have revealed that elevated RDW level was an independent risk factor for unfavorable survival in patients with CRC and bladder cancer (13)(14)(15). Consistent with the previous studies, the results of this study revealed that preoperative elevated RDW-SD level was an unfavorable predictor of PFS and elevated RDW-CV level was related to postoperative complications in patients with CRLM.…”
Section: Nomogram For Os Predictionsupporting
confidence: 90%
“…(9)(10)(11)(12). It has been reported that the red cell volume distribution width (RDW) level of patients with malignant tumours including rectal cancer, colon cancer and bladder cancer is correlated with diagnosis, staging, and prognosis (13)(14)(15). However, no study has revealed the relationship between RDW level and prognosis in patients with CRLM after liver resection, and no nomogram has incorporated preoperative blood markers.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, this parameter was used for the differential diagnosis of anemias. 16 Felker et al found that RDW could serve as an independent predictor of morbidity and mortality in heart failure. 31 Furthermore, many authors have described the link between high RDW and worse prognosis in different types of malignancies such as lung cancer and prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Red blood cell distribution width (RDW) is a parameter that reproduces the volume heterogeneity of RBCs, and it can be obtained from the standard deviation (SD) of erythrocyte volumes for the mean corpuscular volume (MCV) 16 . High RDW values reveal greater size variations of red blood cells, which were reported to be associated with multiple interconnected factors, such as chronic inflammation, prolonged bleeding, or oxidative stress 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Then 73 articles were reviewed in full text to carefully assess the eligibility, 60 of them were further excluded (reasons for exclusion are: other types of urological cancer patients mingled with bladder cancer patients, did not provide measurements of CRP, did not investigate the outcomes of study interest, case-control or cross-sectional design studies, did not use Cox proportional hazards model). In the end, 13 studies were included into our meta-analysis [12][13][14][15][18][19][20][21][22][23][24][25][26].…”
Section: Study Selectionmentioning
confidence: 99%